Study on association of polymorphism of CYP450 2D6 with head and neck cancer and treatment response in patients receiving neoadjuvant chemotherapy paclitaxel, cisplatin, 5fu (TPF) followed by chemoradiation - Kumar, Divyesh; Pant, Mohan Chand; Parmar, Devendra; Singh, Sudhir; Brahmabhatt, Madanlal (International Journal of Research in Medical Sciences, 2017)
Background: Aims of this study were to study the association of genetic polymorphism in CYP450 2D6 in patients of locally advanced head and neck cancer, and try to assess a correlation between this polymorphism & response to treatment. Need of the study was to find out a possible genetic level explanation for the different response achieved in patients with similar histopathology, stage, exposure to carcinogen & ethnicity undergoing similar treatment. Methods: A study comprising of 150 patients & 150 controls was done to analyze the association between polymorphs of CYP450 2D6 with head & neck cancer and treatment response (TPFàCTRT). Two cycles of TPF (paclitaxel-175mg/m2 D1, cisplatin 35mg/m2 D2-D3 and 5Fu 1gm/m2 D1-D3) were given followed by radiotherapy with concurrent cisplatin (40 mg/m2).The response to the treatment was assessed clinically, radiologically & by laryngoscopy-post treatment. Genotyping of the blood samples was done. Analysis of the association between genetic polymorphisms and risk of HNSCC was estimated by calculating crude odds ratio (OR). A P value of <0.05 was considered statistically significant. The statistical analysis was performed with the SPSS software package (version 11.0 for Windows; SPSS Chicago, IL). Results: Patients with CYP 2D6*1 showed good response to the therapy given, while CYP 2D6*4 and *10 were poor responders. Conclusion: There is a strong association of polymorphs of CYP 2D6 with occurrence of head and neck cancer. Response to treatment (TPFàCT-RT) is polymorph graded. Our study thus provides an insight in to the concept of “Right therapy to the right patient”.